1996
DOI: 10.1111/j.1348-0421.1996.tb03320.x
|View full text |Cite
|
Sign up to set email alerts
|

Previous Enteric Adenovirus Infection Does Not Protect against Subsequent Symptomatic Infection: Longitudinal Follow‐up of Eight Infants

Abstract: Eight infants followed longitudinally were found to have enteric adenovirus (EAdv) infections: in 5 infants with diarrhea and in 3 with no accompanying diarrhea. Sequential stool samples prior to EAdv infections were tested for adenovirus antigen, anti-adenoviral IgA and neutralizing antibodies to serotypes 40, 41 and 2 in order to ascertain whether protection from symptoms was due to prior infection. No difference was found in the number of adenoviral infections among infants prior to their EAdv infections wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…That serum NAb could not block re-infection of pathogen from mucosal route was also seen on Ad5 vector in mouse model [41]. Actually, it was Unicomb and the colleagues who dug deepest into this subject although their work is not frequently cited [42]. They found that even the NAb in intestine failed to protect infants from re-infection of enteric adenovirus.…”
Section: Discussionmentioning
confidence: 90%
“…That serum NAb could not block re-infection of pathogen from mucosal route was also seen on Ad5 vector in mouse model [41]. Actually, it was Unicomb and the colleagues who dug deepest into this subject although their work is not frequently cited [42]. They found that even the NAb in intestine failed to protect infants from re-infection of enteric adenovirus.…”
Section: Discussionmentioning
confidence: 90%
“…Astroviruses and adenovirus are important causes of acute gastroenteritis primarily in infants and young children as well as in the elderly and immunocompromised patients (6168). There is limited evidence that protection from both adenovirus and astrovirus infections correlates with mucosal virus-specific IgA in humans (34, 69, 70). These viruses lack small animal models, in which pathogenesis and immunity is similar to that observed in humans.…”
Section: Iga and Protective Immunity Against Gastrointestinal Viral Imentioning
confidence: 99%
“…69,92 Children can become ill when reinfected with EA. 93 However, illness among adults is uncommon, even in outbreak settings where they have a high likelihood of exposure.…”
Section: Diseasementioning
confidence: 99%